Pengaruh FOMO (Fear of missing out) Terhadap Minat Beli Di Common Space Coffee & Bar Batam - Bram Handoko; Wahyudi Ilham; Natal Olotua Sipayung; Dailami . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
This study aims to examine the influence of Fear of FOMO (Fear of missing out) on consumer purchase intention at Café Common Space Batam. FOMO is a psychological phenomenon that manifests as an individual’s urge to follow ongoing trends and avoid the feeling of being left behind. This research applies a quantitative associative-causal approach with a population consisting of all visitors of Common Space Batam over the past six months. The sample size was determined using the Slovin formula with a 10% margin of error, setting the minimum number of respondents at 100, while this study successfully collected 107 valid responses. Data were gathered through a five-point Likert-scale questionnaire and analyzed using simple linear regression. The findings indicate that FOMO has a positive and significant effect on consumers’ purchase intention, with a coefficient of determination (R²) of 0.777 and a significance value of 0.000 (<0.05). These results contribute theoretically to the development of consumer behavior studies and provide practical insights for food and beverage business practitioners in utilizing social media as an effective marketing strategy.